The Emerging Role of the Bone Marrow-Derived Stem Cells in (Therapeutic) Angiogenesis - Carmeliet, Peter; Luttun, Aernout (Thrombosis and Haemostasis, 2001)
Proper formation of blood vessels (angiogenesis) is essential for development, reproduction and wound healing. When derailed, angiogenesis contributes to numerous lifethreatening disorders. While research has generally been focusing on the two main vascular cell types (endothelial and smooth muscle cells), recent evidence indicates that bone marrow may also contribute to this process, both in the embryo and the adult. Novel vascular progenitors, even one common to both endothelial and smooth muscle cells, have been identified in the embryo. An exciting observation is that endothelial precursors have also been identified in the adult bone marrow. Transplantation studies revealed that these precursors as well as other bone marrow-derived cells contribute to the growth of endothelium-lined vessels (angiogenesis) as well as the expansion of pre-existing collaterals (arteriogenesis) in ischemic disease. These findings have raised hopes that bone marrow-derived cells might one day become useful for cell-based angiogenic therapy.
Keywords: Angiogenesis; bone marrow cells; endothelial cells; multipotent progenitors; growth factors